2014
DOI: 10.1093/aob/mcu171
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for land plant cell wall biosynthetic mechanisms in charophyte green algae

Abstract: The results provide new insights into the evolution of cell walls and support the notion that the CGA were pre-adapted to life on land by virtue of the their cell wall biosynthetic capacity. These findings are highly significant for understanding plant cell wall evolution as they imply that some features of land plant cell walls evolved prior to the transition to land, rather than having evolved as a result of selection pressures inherent in this transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 169 publications
(230 reference statements)
3
88
1
Order By: Relevance
“…If living in an aquatic environment, positioning yourself optimally for photosynthesis or your position in the water column is crucial; by contrast, if living terrestrially, different systems are required. Finally, analysis of common streptophyte genes in the K. flaccidum genome identified key physiological adaptations to terrestrial habitats, including oxidative stress, high light, and desiccation [11]. These traits provide the [ 2 1 _ T D $ D I F F ] algae with a competitive advantage in the terrestrial environment, as does the cell wall features identified by our genomic analysis.…”
Section: Does Previously Published Data Now Make More Evolutionary Sementioning
confidence: 73%
See 2 more Smart Citations
“…If living in an aquatic environment, positioning yourself optimally for photosynthesis or your position in the water column is crucial; by contrast, if living terrestrially, different systems are required. Finally, analysis of common streptophyte genes in the K. flaccidum genome identified key physiological adaptations to terrestrial habitats, including oxidative stress, high light, and desiccation [11]. These traits provide the [ 2 1 _ T D $ D I F F ] algae with a competitive advantage in the terrestrial environment, as does the cell wall features identified by our genomic analysis.…”
Section: Does Previously Published Data Now Make More Evolutionary Sementioning
confidence: 73%
“…Comparative genomics of 'primitive' and higher plants established genetic orthology between all the major polysaccharides in embryophytes [10]. Using transcriptomes instead of genomes, orthology was also established between land plants and charophytes [11]. Evidence for rosette-forming cellulose synthases was found as far back as in Chlorokybus, a very early divergent charophyte.…”
Section: The Cell Wall Provides Cluesmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between cell elongation and ethylene in algae has been largely unexplored, despite extensive research on cell wall composition and evolution in algae (Sørensen et al, 2010;Mikkelsen et al, 2014). Cellular elongation requires relaxation of the cell wall in order to facilitate turgor-driven longitudinal expansion (Cosgrove, 2000).…”
Section: Ethylene Regulates Spirogyra Cell Wall Modificationmentioning
confidence: 99%
“…Phylogenetic analyses have suggested to some investigators that streptophyte CSC‐encoding genes might have had a common origin before divergence into separate clades (Mikkelsen et al. ). Chlorophytes and streptophytes also differ in other cell‐wall carbohydrate polymers, such as hemicelluloses and matrix carboxylic polysaccharides.…”
mentioning
confidence: 99%